Charting the use of mini-clinical evaluation exercise (mini-CEX) in nursing and dental education: a bibliometric analysis from the Web of Science database - Sim, Galvin Siang Lin; Ying, Annabell Ying Sim; Sana, Erlyn Aclan; Johnson, Gideon U (Yeungnam University School of Medicine and College of Medicine, 2025)
Background: Workplace-based assessments, such as the mini-clinical evaluation exercise (mini-CEX), are increasingly used to evaluate clinical competence in authentic healthcare settings. This study aimed to map and evaluate the global research landscape of mini-CEX in nursing and dental education through bibliometric analysis.